Dim Blue Light at Night Induces Spatial Memory Impairment in Mice by Hippocampal Neuroinflammation and Oxidative Stress - Qi Liu; Zixu Wang; Jing Cao; Yulan Dong; Yaoxing Chen (MDPI AG, 2022)
Light pollution is one of the most serious public problems, especially the night light. However, the effect of dim blue light at night (dLAN-BL) on cognitive function is unclear. In this study, we evaluated the effects of exposure to dLAN-BL in C57BL/6J mice for 4 consecutive weeks. Our results showed dLAN-BL significantly impaired spatial learning and memory and increased plasma corticosterone level in mice. Consistent with these changes, we observed dLAN-BL significantly increased the numbers and activation of microglia and the levels of oxidative stress product MDA in the hippocampus, decreased the levels of antioxidant enzymes Glutathione peroxidase (GSH-Px), Superoxide dismutase (SOD), Gluathione reductase (Gsr), total antioxidants (T-AOC) and the number of neurons in the hippocampus, up-regulated the mRNA expression levels of IL6, TNF-α and the protein expression levels of iNOS, COX2, TLR4, p-p65, Cleaved-Caspase3 and BAX, and down-regulated the mRNA expression levels of IL4, IL10, Psd95, Snap25, Sirt1, Dcx and the protein expression level of BCL2. In vitro results further showed corticosterone (10uM)-induced BV2 cell activation and up-regulated content of IL6, TNF-α in the cell supernatant and the protein expression levels of iNOS, COX2, p-p65 in BV2 cells. Our findings suggested dLAN-BL up-regulated plasma corticosterone level and hippocampal microglia activation, which in turn caused oxidative stress and neuroinflammation, leading to neuronal loss and synaptic dysfunction, ultimately leading to spatial learning and memory dysfunction in mice.